Cost and turn-around time display decreases inpatient ordering of reference laboratory tests: a time series. Issue 12 (27th August 2014) - Fang, Daniel Z; Sran, Gurmeet; Gessner, Daniel; Loftus, Pooja D; Folkins, Ann; Christopher, John Y; Shieh, Lisa
Abstract : Objective: Reference tests, also known as send-out tests, are commonly ordered laboratory tests with variable costs and turn-around times. We aim to examine the effects of displaying reference laboratory costs and turn-around times during computerised physician order entry (CPOE) on inpatient physician ordering behaviour. Design: We conducted a prospective observational study at a tertiary care hospital involving inpatient attending physicians and residents. Physician ordering behaviour was prospectively observed between September 2010 and December 2012. An intervention was implemented to display cost and turn-around time for reference tests within our CPOE. We examined changes in the mean number of monthly physician orders per inpatient day at risk, the mean cost per order, and the average turn-around time per order. Results: After our intervention, the mean number of monthly physician orders per inpatient day at risk decreased by 26% (51 vs 38, p<0.0001) with a decrease in mean cost per order (US$146.50 vs US$134.20, p=0.0004). There were no significant differences in mean turn-around time per order (5.6 vs 5.7 days, p=0.057). A stratified analysis of both cost and turn-around time showed significant decreases in physician ordering. The intervention projected a mean annual savings of US$330 439. Reference test cost and turn-around time variables were poorly correlated (r=0.2). These findings occurred in the setting of non-significant change to physician ordering in a control cohort of non-reference laboratory tests. Conclusions: Display of reference laboratory cost and turn-around time data during real-time ordering may result in significant decreases in ordering of reference laboratory tests with subsequent cost savings.